2009
DOI: 10.1293/tox.22.11
|View full text |Cite
|
Sign up to set email alerts
|

Biological Basis of Differential Susceptibility to Hepatocarcinogenesis among Mouse Strains

Abstract: There is a vast amount of literature related to mouse liver tumorigenesis generated over the past 60 years, not all of which has been captured here. The studies reported in this literature have generally been state of the art at the time they were carried out. A PubMed search on the topic “mouse liver tumors” covering the past 10 years yields over 7000 scientific papers. This review address several important topics related to the unresolved controversy regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 184 publications
(187 reference statements)
4
45
0
Order By: Relevance
“…The mechanistic basis for the sex difference in the extent of PB-induced hepatocyte proliferation and the apparent noninvolvement of CYP2B in the proliferative response in females are currently not understood, but they may be partly explained by the lower extent of hepatic CYP2B induction by PB in females than in males. In that regard, our present result was consistent with previous reports, that PB induced CYP2B10 to a larger extent in males than in females (Li-Masters and Morgan, 2001;Stamou et al, 2014) and that male mice were more susceptible to PB-induced hepatocarcinogenesis than female mice (Heindryckx et al, 2009;Maronpot, 2009). This sex difference in CYP2B inducibility by PB does not appear to be due to a difference in CAR expression, because cytosolic (Hernandez et al, 2009) or nuclear (Saito et al, 2013) CAR protein level was found to be similar between untreated male and female mice.…”
Section: Cyp2b and Pb-induced Hepatocyte Proliferationsupporting
confidence: 93%
“…The mechanistic basis for the sex difference in the extent of PB-induced hepatocyte proliferation and the apparent noninvolvement of CYP2B in the proliferative response in females are currently not understood, but they may be partly explained by the lower extent of hepatic CYP2B induction by PB in females than in males. In that regard, our present result was consistent with previous reports, that PB induced CYP2B10 to a larger extent in males than in females (Li-Masters and Morgan, 2001;Stamou et al, 2014) and that male mice were more susceptible to PB-induced hepatocarcinogenesis than female mice (Heindryckx et al, 2009;Maronpot, 2009). This sex difference in CYP2B inducibility by PB does not appear to be due to a difference in CAR expression, because cytosolic (Hernandez et al, 2009) or nuclear (Saito et al, 2013) CAR protein level was found to be similar between untreated male and female mice.…”
Section: Cyp2b and Pb-induced Hepatocyte Proliferationsupporting
confidence: 93%
“…Interestingly, all these agents also induced cancer in other sites than the liver. These results confirm the finding that different strains of rats and mice present a different susceptibility to the development of HCC (Feo et al, 2009;Maronpot 2009). It should be noted that recent studies on genetic susceptibility and epigenetic regulation of the signaling pathways involved in hepatocarcinogenesis in rats have shown that most alterations responsible for a resistant or susceptible phenotype in rats also have a similar contribution to the prognosis of human HCC (Feo et al, 2009).…”
Section: Long-term Carcinogenicity Bioassays As a Tool To Identify Posupporting
confidence: 90%
“…This represented a statistically significant increase compared to controls, even when preneoplastic lesions were excluded from the analysis. It is also noteworthy that hepatic tumors occurred in the absence of additional carcinogenic insult even though this study used the C56BL/6 mouse strain, a model that is considered “relatively resistant” to hepatocellular carcinoma [139]. It should be noted, however, that the doses of BPA used to achieve significant induction of liver pathologies were above the RfD, yet female offspring exhibited a significant linear dose-response for combined neoplastic and preneoplastic lesions [138].…”
Section: Cancers In Non-reproductive Estrogen Target Tissuesmentioning
confidence: 99%